1998
DOI: 10.1074/jbc.273.31.19817
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of a Single Lysine Mutation and a C-terminal Domain in the Cytoplasmic Sequestration of the p53 Protein

Abstract: Cytoplasmic sequestration of the p53 tumor suppresser protein has been proposed as a mechanism involved in abolishing p53 function. However, the mechanisms regulating p53 subcellular localization remain unclear. In this report, we analyzed the possible existence of cis-acting sequences involved in intracellular trafficking of the p53 protein. To study p53 trafficking, the jellyfish green fluorescent protein (GFP) was fused to the wild-type or mutated p53 proteins for fast and sensitive analysis of protein loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 39 publications
2
45
1
2
Order By: Relevance
“…However, because mutations were not confirmed with DNA sequencing, these data should be interpreted with caution. Liang et al 14 used colon and breast cancer cell lines and found that a p53 mutation in codon 305 was related to the p53 protein being sequestered to the cytoplasm. They further demonstrated that, together with a cytoplasmic sequestration domain at the C-terminus (amino acid 326 to 355) of the p53 protein, lysine 305 was necessary for nuclear import of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…However, because mutations were not confirmed with DNA sequencing, these data should be interpreted with caution. Liang et al 14 used colon and breast cancer cell lines and found that a p53 mutation in codon 305 was related to the p53 protein being sequestered to the cytoplasm. They further demonstrated that, together with a cytoplasmic sequestration domain at the C-terminus (amino acid 326 to 355) of the p53 protein, lysine 305 was necessary for nuclear import of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…As p53 is too large to passively di use across the nuclear pore, its subcellular distribution must be mediated by the cell's protein import and export machinery. Facilitated nuclear import of p53 occurs via three lysine-rich nuclear localization signals (NLSs) in the Cterminus at amino acids 305±322 (NLS I), 369-375 (NLS II), and 379±384 (NLS III) (Liang et al, 1998;Shaulsky et al, 1990b). NLS I appears to be the primary NLS as mutation of this sequence alone abrogates p53 nuclear import.…”
Section: Linking P53 Activation With Its Subcellular Localizationmentioning
confidence: 99%
“…The cdc2/cdk2 phosphorylation site at S315 and the PCAF acetylation site at K320 both lie within NLS I, and it is not di cult to imagine that these modi®cations could a ect association with a nuclear import receptor, especially since the phosphorylation of NLSs has been reported to regulate the import of other proteins such as SWI5 (Jans et al, 1995;Moll et al, 1991), Lamin B2 (Hennekes et al, 1993), v-Jun (Tagawa et al, 1995, and CaM kinase II (Heist et al, 1998). However, since an S315A mutation seems to have no e ect on p53 nuclear localization (Liang et al, 1998), it remains to be determined what role these modi®cations may play.…”
Section: Linking P53 Activation With Its Subcellular Localizationmentioning
confidence: 99%
“…In the C-terminal domain, nuclear-localization signals mediate translocation of p53 to the nucleus (Shaulsky et al, 1990;Liang et al, 1998). Post-translational modifications of this region modulate the specific activity of p53 in vivo and, in unstressed cells, the C-terminal domain maintains p53 in a non-DNA-binding form (Levine, 1997;Hupp et al, 2000).…”
Section: Introductionmentioning
confidence: 99%